Editorial do dossiê “Reformas da investigação preliminar e a investigação defensiva no processo penal”. Investigação preliminar: desafios e perspectivas = Editorial of dossier “Reforms in criminal investigation and defensive investigation in criminal procedure”. Preliminary investigation: challenges and perspectives - Saad, Marta (2020)
DOI: https://doi.org/10.22197/rbdpp.v6i1.348